Evaluation of Compatibility of a Gum Mastic Liquid Adhesive and Liquid Adhesive Remover With an Alcoholic Chlorhexidine Gluconate Skin Preparation. Issue 4 (July 2017) - Ryder, Marcia; Duley, Collette
Abstract : The compatibility of a 2% chlorhexidine gluconate/70% isopropyl alcohol (CHG/IPA) skin preparation with a gum mastic liquid adhesive (GMLA) and liquid adhesive remover (LAR) was assessed in healthy volunteers. Twenty subjects completed test material combination with microbial sampling at 3- and 7-day time points. Mean log10 reductions from baseline for normal flora were assessed. There was no significant difference in reduction of normal flora on skin prepped with CHG/IPA versus skin prepped with CHG/IPA followed by GMLA or LAR. The conclusion of the study was that the use of GMLA or LAR with CHG/IPA does not affect the antiseptic effectiveness of CHG/IPA.